Remedial Programs' Effectiveness on Indonesian Language Learning at SMAN 1 Bandar Baru, Pidie Jaya Regency - Rahmi, Hayatun; Jafaruddin, Jafaruddin; Iqbal, Muhammad (Budapest International Research and Critics University, 2021)
This research aims to examine the use of remedial education in achieving completeness in Indonesian language education subjects, as well as to provide an overview and information on the use of remedial education on student learning difficulties in class XI SMAN 1 Bandar Baru Pidie Regency for the 2019/2020 academic year.NThe key concern addressed in this study is how the improvement program in Indonesian language learning is implemented and influenced in class X1 of SMAN 1 Bandar Baru, Pidie Jaya Regency, for the academic year 2019/2020. This study employs a quantitative method based on the product-moment formula to answer this question. The acquired data will be triangulated, including questionnaire data triangulation, interviews, and documentation.The findings of this study show that (a) remedial learning occurs when the categories of student learning issues are identified. (b) as a subject that instructs and guides pupils in learning and comprehending Indonesian language instruction. (c) it is discovered that remedial learning has a considerable impact on learning issues following implementation. Based on experiments utilizing the product moment formula, it was discovered that the remedial program had a considerable influence on learning challenges in Indonesian language education, as indicated by the r count of 0.763 from the r table, both at the 1% level (0.361 percent).Â